The diagnostic accuracy of different fetal blood sample lactate cutoffs in labor, utilizing the StatStrip Xpress® lactate‐meter: A population‐based observational study - Magnus B. Berge; Jørg Kessler; Anne Cathrine Staff; Anne Flem Jacobsen (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction A recent study recommended 5.2 mmol/L as a cutoff for fetal blood sample (FBS) lactate in labor for the StatStrip Lactate®/Lactate Xpress® lactate meter. In the present study, we validated FBS lactate cutoffs in a larger population‐based setting, with different CTG guidelines, testing external validity. Material and Methods We conducted a prospective population‐based study at Oslo University Hospital, Ullevål, Norway, a tertiary referral obstetric department with 7000 annual deliveries. Women with a singleton fetus in cephalic presentation in gestational week ≥36 + 0 were included in the analyses. We used ROC curves to calculate the area under the curve (AUC) and estimate the optimal cutoff for the following adverse neonatal outcomes: Umbilical cord pH ≤7.10, umbilical cord pH ≤7.05, metabolic acidosis (pH <7.0 and Base deficitextracellular fluid > 12 mmol/L), 1‐minute Apgar score <4, 5‐min Apgar score <7, hypoxic ischemic encephalopathy, and transfer to the neonatal intensive care unit. Analyses were restricted to women with a FBS lactate within 25 min prior to delivery. The study is registered in clinicaltrials.gov (ClinicalTrials.gov Identifier: NCT04779294). Results Of 7816 included women, 1466 (19%) had a FBS lactate measurement within 25 min prior to delivery. The calculated optimal cutoff for FBS lactate varied by outcomes: 5‐min Apgar score <7: AUC 0.69 (0.57–0.80), cutoff 4.0 mmol/L; metabolic acidosis: AUC 0.92 (0.78–1.00), cutoff 7.0 mmol/L; hypoxic ischemic encephalopathy: AUC 0.95 (0.86–1.00), cutoff 4.7 mmol/L. Sensitivity increased for some of the outcomes with a decreasing cutoff. Specificity increased for all outcomes with an increasing cutoff. Conclusions We consider an FBS lactate cutoff of ≥5.2 mmol/L a good balance between high sensitivity for adverse neonatal outcomes and an acceptable number of needed interventions.